MEKANISME PENETAPAN SAHAM SYARIAH DALAM KETEGORI INDEKS SAHAM SYARIAH INDONESIA (ISSI) PADA BURSA EFEK INDONESIA (BEI) SURABAYA - Khoirin Andi, Ahmad (Program Studi Hukum Keluarga Islam, 2023)
Determination of sharia shares conducted by the Indonesia Stock Exchange is carried out 2 (two) times a year, namely in June and December with due regard to the issuer's operations. In determining sharia shares, the Indonesia Stock Exchange first submits a list of names of issuers that will be submitted at a joint determination meeting with the Financial Services Authority (OJK) and also the National Sharia Board - Indonesian Ulema Council (DSN-MUI). The determination of sharia shares refers to regulations and fatwas that have been issued by these institutions. Issuers who do not meet the criteria for sharia shares will be issued in the List of Sharia Securities (DES), while issuers that qualify as sharia shares will be included in DES. (2) Factors that affect shares can be categorized as sharia shares are issuers whose operations do not engage in production, service and income activities that are prohibited by Islam, namely usury, maysir, gharar, gambling, and products produced which are forbidden by religion. As well as the articles of association of a listed company remain in sharia principles.